Response of Litter Decomposition and Nutrient Release Characteristics to Simulated N Deposition in Pinus yunnanensis Franch. Forest in Central Yunnan Plateau - Nian, Yaoping; Chen, Wen; Zhao, Yangyi; Hou, Zheng; Zhang, Long; Liang, Xiaoling; Song, Yali (Forests, 2025)
Nitrogen deposition can significantly impact soil biogeochemical cycling; however, its effects on the decomposition processes and nutrient release from leaf and twig litter in subtropical plantations remain inadequately understood. In this study, we focused on the Pinus yunnanensis Franch. forest in the central Yunnan Plateau, southwestern China, and explored how nitrogen addition influences litter decomposition nutrient release over two years, under four levels: control (CK, 0 g·m−2·a−1), low nitrogen (LN, 10 g·m−2·a−1), medium nitrogen (MN, 20 g·m−2·a−1), and high nitrogen (HN, 25 g·m−2·a−1). The results indicate that after 24 nitrogen application treatments, the rates of remaining mass in both leaf and twig litters followed the pattern: LN < CK = MN < HN. Under all nitrogen application treatments, the rate of remaining mass in leaf litters was significantly lower than that of twig litters (p < 0.05). Under LN, the mass retention in leaf and twig litters decreased by 3.96% and 8.41%, respectively, compared to CK. In contrast, under HN treatments, the rates of remaining mass in leaf and twig litters increased by 8.57% and 5.35%, respectively. This demonstrates that low nitrogen accelerates decomposition, whereas high nitrogen inhibits it. Significant differences in the remaining amounts of lignin and cellulose in both leaf and twig litters were observed when compared to CK (p < 0.05). Additionally, decomposition time and nitrogen deposition had significant effects on the remaining rates of nutrients (C, N, P) and their C/N, C/P, and N/P in litters (p < 0.05). Following nitrogen application, the C/N of the litters significantly reduced, while the N/P increased. The results suggest that nitrogen addition alleviates the nitrogen limitation on the litters while intensifying the phosphorus limitation.